ANALISIS PENGARUH KOMPENSASI FINANSIAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN DISIPLIN KERJA DAN MOTIVASI BERPRESTASI SEBAGAI VARIABEL (Studi pada Badan Narkotika Nasional Provinsi Jawa Tengah) - Prasetya, Sindhi Saraayu; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2016)
Organizational Citizenship Behavior (OCB) is a behavior that needs to be owne d b y c ivil servants. Many ways can be done to improve the Organizational Citizenship Behavior ( O C B) o ne with a financial compensation. Financial compensation were able to improve work discip line a nd motivation of achievement, so it can affect the Organizational Citizenship Behavior (OCB) employees. The purpose of this study is to describe and analy ze further on the influence of financial compensation on Organizational Citizenship Behavior (OCB) with the discipline of work and achievement motivation as an intervening variable.Data collection methods used in this study is a questionnaire with a sample of 74 employees BNNP Jawa Tengah, which uses a sample of the entire population census or using BNNP Jawa Tengah employees. Data analysis method used is multiple linear regression ana lys is . Mechanical testing data used in this study include path analysis and sobel test to test th e e f fec t o f mediation.The results of this study indicate that financial compensation negative a n d s ig nific ant to work discipline and a positive and significant to motivation of achiev eme n t. Th en th e f ina nc ial compensation and work discipline positive and significant impact on Organizationa l C itiz e ns hip Behavior (OCB), while the achievement motivation did not significantly affect to O r ga niz atio nal Citizenship Behavior (OCB). In addition, work discipline and motivation of achiev e me nt c a n n ot mediate the relationship between financial compensation on Organizational Citizenship Be ha vio r (OCB).